EFEKTIVITAS MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA POKOK BAHASAN SISTEM PERNAPASAN MANUSIA - Tabitha Sri Hartati Wulandari; Muhammad Shohibul Ihsan; Ferry Yudha Pratama; Sri Cacik (Jurnal Inovasi Pendidikan dan Sains, 2023)
This research aims to improve students' critical thinking by using Discovery Learning model on Human Respiratory System. The type of research used is quantitative descriptive research. The research method chosen was pre-experimental with a one group pretest-posttest research design. Pretest was carried out to determine the research subjects' critical thinking before the Discovery Learning model was given. After treatment, the research subjects' critical thinking was determined based on posttest scores. The research subjects were 34 students of PGSD FKIP Universitas PGRI Ronggolawe Tuban who were taking the first semester of the 2023/2024 academic year. The research instrument used to collect data was a critical thinking test using 25 multiple choice questions. Analysis of research data using N-Gain Score. The research results show that the average percentage of N-Gain Score is 72% or in the high category. Apart from that, the average critical thinking score also increased during the pretest and posttest, namely from 57 to 88. Based on the analysis of research data, it can be concluded that the application of the Discovery Learning model can improve the critical thinking of research subjects. Therefore, further research is related the application of the Discovery Learning model can be accompanied by innovative learning media, so that the effectiveness obtained is maximized.